2002
DOI: 10.1128/iai.70.9.4859-4869.2002
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Lsp, a Member of the LraI-Lipoprotein Family inStreptococcus pyogenes, in Eukaryotic Cell Adhesion and Internalization

Abstract: Three open reading frames (ORFs) were identified by a genome walking strategy in the genomes of serotype M49 group A streptococcal (GAS) strains CS101 and 591. These ORFs were located between the mga core regulon and the dipeptide permease operon. The deduced amino acid (aa) sequences contained signature sequences indicative of a lipoprotein (306 aa), an intracellular protein (823 aa), and a secreted peptide (66 aa), respectively. ORF1 (named Lsp for lipoprotein of Streptococcus pyogenes) and ORF2 exhibited a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 62 publications
3
68
0
Order By: Relevance
“…It has been previously reported that an Lsp-null mutant had a reduced ability to adhere to epithelial cells, suggesting that Lsp may act directly as an adhesin to recognize a host cell receptor (23). It was also noted that the Lsp Ϫ mutant had reduced expression of several virulence factors, including PrtFII, a fibronectin-binding adhesin (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously reported that an Lsp-null mutant had a reduced ability to adhere to epithelial cells, suggesting that Lsp may act directly as an adhesin to recognize a host cell receptor (23). It was also noted that the Lsp Ϫ mutant had reduced expression of several virulence factors, including PrtFII, a fibronectin-binding adhesin (23).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the case for PsaA Ϫ mutants of S. pneumoniae (5, 71), Lsp Ϫ mutants of S. pyogenes have a defect in their ability to adhere to cultured host cells (23). However, subsequent analyses of PsaA Ϫ mutants have suggested that the adherence defect is an indirect result of an imbalance in metal homeostasis promoted by the loss of PsaA (43).…”
Section: Vol 77 2009 S Pyogenes Lsp Is Required For Zinc Homeostasmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, this protein shows similarities to an adhesin family known as LraI found initially in oral streptococci (Jenkinson, 1994) and since then discovered in other streptococci and other genera (Cockayne et al, 1998). It was suggested that LraI-like proteins are involved in the colonization of human epithelium by streptococci and their subsequent invasion into the bloodstream (Elsner et al, 2002). It is not clear why yfnA, lmb and phtD are associated in an operon system.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, bacterial lipoproteins are also involved in adhesion to and invasion of epithelial cells (42). For example, the surface-exposed lipoprotein JlpA specific to Campylobacter jejuni mediates adherence to HEp-2 epithelial cells and Lsp, which belongs to the LraI lipoprotein family, is involved in Streptococcus pyogenes adhesion to and invasion of A549 cells (11,16).…”
mentioning
confidence: 99%